2014
DOI: 10.1186/1472-6785-14-13
|View full text |Cite
|
Sign up to set email alerts
|

Individual quality explains association between plumage colouration, arrival dates and mate acquisition in yellow warblers (Setophaga petechia)

Abstract: BackgroundIn many bird species colour traits influence social dominance and breeding success. In our study we first evaluated whether the colour of the basic plumage (tail feathers grown at the end of the breeding season), that provides an index of individual quality, influenced winter habitat use by yellow warblers. We then evaluated whether winter habitat use (inferred using δ13C and δ15N signatures of winter grown greater-coverts) influenced alternate plumage colouration, after controlling for individual qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Analysis of return rates was done using generalized linear mixed-effects models with a binomial distribution, controlling for individual (band number) and year as random factors. Significance was determined by comparing the fit of the models with and without the terms of interest using likelihood ratio tests (as in Jones et al 2014). Subsequent-year productivity was analyzed using a zero-adjusted Poisson (ZAP) or hurdle model, similar to Jones et al (2014), due to the high distribution of zeros and few repeat measures (no random effect of individual).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of return rates was done using generalized linear mixed-effects models with a binomial distribution, controlling for individual (band number) and year as random factors. Significance was determined by comparing the fit of the models with and without the terms of interest using likelihood ratio tests (as in Jones et al 2014). Subsequent-year productivity was analyzed using a zero-adjusted Poisson (ZAP) or hurdle model, similar to Jones et al (2014), due to the high distribution of zeros and few repeat measures (no random effect of individual).…”
Section: Methodsmentioning
confidence: 99%
“…Significance was determined by comparing the fit of the models with and without the terms of interest using likelihood ratio tests (as in Jones et al 2014). Subsequent-year productivity was analyzed using a zero-adjusted Poisson (ZAP) or hurdle model, similar to Jones et al (2014), due to the high distribution of zeros and few repeat measures (no random effect of individual). These models are suitable for data with a high proportion of true zero values (cf.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, ornament production has been linked to over-wintering conditions in both pied (Ficedula hypoleuca) and collared flycatchers (Ficedula albicollis), which also molt in sub-Saharan Africa (Garant, Sheldon, & Gustafsson, 2004;Järvistö, Calhim, Schuett, & Laaksonen, 2016). In North America, yellow warblers (Setophaga petechia) undergo a pre-alternate molt of body feathers on the wintering grounds; birds overwintering in higher-quality habitat (inferred via stable isotope analysis) produced more colorful feathers (higher chroma), which are important for mate choice during breeding (Jones, Drake, & Green, 2014). Though American redstarts molt near the breeding grounds, Reudink et al (2015) demonstrated that over an 11-year period, the amount of rainfall experienced during the postbreeding molt was associated with carotenoid-based tail coloration in the subsequent season.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, early males mate more successfully (Aebischer et al 1996, Lozano et al 1996, Smith and Moore 2005, Zając et al 2006, Sergio et al 2007), benefit from polygynous (Alatalo et al 1984, Hasselquist 1998, Canal et al 2021) and extrapair matings (Langefors et al 1998, Møller et al 2003, Cooper et al 2011) or both (Reudink et al 2009a, Canal et al 2012). The time of male arrival is often related to the attractiveness of sexual signals, such as song (Arvidsson and Neergaard 1991, Lampe and Espmark 1994, Kipper et al 2006) and plumage traits (Slagsvold and Lifjeld 1988, Møller 1994, Ninni et al 2004, Jones et al 2014).…”
Section: Introductionmentioning
confidence: 99%